Use of bone callus as a source of bone graft for concurrent tibial malunion repair and contralateral pantarsal arthrodesis in a domestic shorthair cat—a case report - Tian, Gracia; Tuan, Jayson (Frontiers in Veterinary Science, 2026)
A domestic shorthair cat, estimated 1 year old, was presented from a local rescue with traumatic injuries of unknown cause to both pelvic limbs. Radiographs revealed a left tibial malunion with marked callus formation and complex right tarsocrural joint injuries. A modified chipping technique was used to provide a source of autogenous bone graft from the callus for both the malunion correction and the contralateral pantarsal arthrodesis. Post-operative radiographs showed significant improvement in the left tibial alignment and adequate arthrodesis of the right tarsal joints. There was good functional outcome at 3 months post-operatively. This case report highlights the potential of bone callus to be used as a bone graft, presenting a unique technique to avoid donor site morbidity associated with traditional autogenous bone grafts. The modified chipping technique can also be employed in malunion revision surgeries to effectively correct resultant angular deformities while preserving the fracture haematoma. To the authors' knowledge these have not been reported in the veterinary literature.